Nilai Moral Dalam Novel Ning Anak Wayang Karya Niken dan Anjar Kajian: Sosiologi Sastra - Fitri Auliani; Rosliana Lubis; Emma Marsella (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research is motivated by the importance of moral values in everyday life. Moral values aim to shape human character or morals into a good person. This study aims to describe the moral values contained in the novel Ning Anak Wayang by Niken and Anjar study: Sociology of Literature. This study uses a qualitative descriptive method. The results of this study indicate that researchers use the theory according to Wicaksono (2014: 276-281) which states that moral values consist of several sub-values, namely: the relationship between humans and their God, the relationship between humans and themselves, and the relationship between humans and other humans in the social sphere.